Micronized milo and urea in high-hay growing rations for beef heifers - K. Bolsen; Jack G. Riley (Kansas Agricultural Experiment Station Research Reports, 1976)
Twenty-four individually fed heifers were used to evaluate four combinations of micronized or dry-rolled milo and soybean meal or urea supplements in prairie hay growing rations. Feeding 5 lbs. of micronized milo produced 23% faster and 18% more efficient gains than feeding 5 lbs. of dry-rolled milo. Heifers fed micronized milo + urea tended to gain faster and more efficiently than heifers fed dry-rolled milo + soybean meal.
Keywords: Cattlemen' s Day; 1976; Report of progress (Kansas State University. Agricultural Experiment Station); 262; Beef; Micronized milo; Urea; Rations; Heifers